The Hazards of Growing Up: A Study of the Changing Mechanisms of Bullying Among Girls in Shenzhen - Tam, Frank Wai-ming; Zhang, Sophia Zhao-qin (Alberta Journal of Educational Research, 2012)
Among the many contending theories of bullying, the widely accepted thesis known as frustration-aggression assumes that bullying is a form of aggressive behavior induced by external stress. Recently, researchers have discovered that the relationship between external stressors and bullying is sometimes moderated by internal frustration. The present investigation is an attempt to examine which of the above mechanisms can better explain female students’ bullying behaviors. Data analysis, using structural equation modeling, was based on 1,069 girls selected from 14 primary schools and 16 junior secondary schools in Shenzhen, China. The result of the analysis suggests that while bullying by girls in primary schools is directly related to external stress, bullying in secondary schools is moderated by internal frustration. The authors suggest that several risk factors, namely, (a) the competitiveness of the education system, (b) socialization processes within families and schools, and (c) developmental changes in females during puberty, may be contributing to the difference between bullying mechanisms in primary and secondary schools. Parmi les nombreuses théories contraires portant sur l'intimidation, la thèse largement acceptée, connue sous le nom de frustration-agression postule que l'intimidation est une forme de comportement agressif provoqué par le stress externe. Les chercheurs ont récemment découvert que le rapport entre les agents de stress externes et l'intimidation est parfois modéré par la frustration interne. La présente étude vise à déterminer lesquels de ces mécanismes expliquent le mieux les comportements d'intimidation par les élèves. L'analyse de données, suivant la modélisation par équation structurelle, était basée sur 1 069 filles sélectionnées de 14 écoles primaires et 16 écoles secondaires à Shenzhen, en Chine. Les résultats de l'analyse donnent à penser que l'intimidation par les filles à l'école primaire est directement liée au stress externe, alors que l'intimidation à l'école secondaire est modérée par la frustration interne. Les auteurs proposent qu'il est possible que plusieurs facteurs de risque, notamment (a) la compétitivité du système d'éducation, (b) les processus de socialisation en sein des familles et des écoles et (c) les changements de croissance chez les filles pendant la puberté, contribuent aux différences entre les mécanismes d'intimidation à l'école primaire et à l'école secondaire.